Development of predictive heart risk score : A predictive mobile apps - Sajid, Mirza Rizwan; Noryanti, Muhammad; Khan, Arshad Ali (2021)
Predictive Model of Heart Risk Score. Non-Laboratory-Based Heart Risk Score (NLHRS) Apps has been developed based on risk prediction models produced from novel machine learning (ML) methodology. The NLHRS Apps recommended formal risk assessment tool to assess cardiovascular diseases (CVDs) risk for the primary prevention of CVDs in people. This apps contains 14 variables/features which are used to determine weather a person has CVDs.